Picasso's war the destruction of Guernica and the masterpiece that changed the world - Martin, Russell 1952- (Dutton, a member of Penguin Putnam Inc., 2002)
On April 26, 1937, the Basque town of Guernica in northern Spain was bombed by Hitler's Luftwaffe in the midst of a bloody civil war on behalf of Francisco Franco's rebel forces. Twenty-four hours later, the village lay in ruins, its population decimated. This act of terror and unspeakable cruelty--the first large-scale attack against civilians in modern warfare-outraged the world, and one man in particular. Pablo Picasso, an expatriate living in Paris, responded to the devastation in his homeland by beginning work on Guernica, a painting that many today consider the greatest artwork of the twentieth century.